Medical negligence litigation as a mechanism for understanding gaps in health system responsiveness in the South African public health system - Kolawole, Omowamiwa (Department of Public Health and Family Medicine, 2024)
Medical negligence claims in South Africa have seen a significant rise in recent years. The reasons given for this rise have ranged from accusations of predatory legal practitioners taking advantage of patients to an ever-increasing quantum of damages been awarded by the courts. The impact of this rise in cases has particularly been felt by public health systems, who are having to dedicate considerable resources to defending the claims made against their workers and facilities, as well as make the pay-outs for damages awarded against them. The increase in medical negligence cases has been viewed as an unwelcome and expensive hinderance to the proper functioning of these public health systems, leading to calls by health system leadership for an overhaul of the laws governing medical negligence claims and possible legal remedies including damages. While procedural interventions may be helpful in reducing the cost of medico-legal claims for the public health system, they do not address the underlying challenge of untoward health outcomes that are the basis of subsequent negligence claims. However, health systems leaders rarely give countenance to the possibility that the increase of medical negligence claims is a response to weak health systems, lacking in their ability to meet their obligations to health users. While these obligations include quality health care delivery with favourable biomedical outcomes, they also entail appropriate response to legitimate citizen expectations (health system responsiveness). An exploratory qualitative interdisciplinary study, using case law analysis was carried out to analyse medical negligence case law in South Africa and to identify possible health system responsiveness lapses. Five aspects of responsiveness emerged in the findings from the analysis of the case law, with dignity being the health system responsiveness category most often breached, as recalled by health users in their medical negligence claims. This exploratory study raises the possibility of viewing medical negligence cases as a mechanism for informing lapses in health system responsiveness. Such a responsiveness-minded analysis of health user claims can help in an understanding of patient dissatisfaction as being as much about desires for a more responsive health system as it is about seeking recompense for untoward health outcomes.